2000
DOI: 10.1097/00000478-200003000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the Gastroesophageal Junction

Abstract: Current diagnostic criteria for reflux disease and Barrett's esophagus are based on the belief that the gastroesophageal junction normally contains 2 cm of cardiac mucosa composed of mucous glands devoid of parietal cells. This autopsy study disproves this belief. Even when the entire circumference of the gastroesophageal junction is examined, pure cardiac mucosa was completely absent in 56% of patients. All patients had oxyntocardiac mucosa, in which glands contained a mixture of mucous and parietal cells. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
162
2
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(180 citation statements)
references
References 9 publications
8
162
2
8
Order By: Relevance
“…Some investigators believe that cardiac mucosa is not normal mucosa but, rather, mucosa acquired as a result of gastroesophageal reflux [10]. Gastroesophageal reflux disease (GERD) occurs less frequently in Japan than in the Western world, but in our study, cardiac mucosa was seen in most patients.…”
Section: Discussioncontrasting
confidence: 63%
“…Some investigators believe that cardiac mucosa is not normal mucosa but, rather, mucosa acquired as a result of gastroesophageal reflux [10]. Gastroesophageal reflux disease (GERD) occurs less frequently in Japan than in the Western world, but in our study, cardiac mucosa was seen in most patients.…”
Section: Discussioncontrasting
confidence: 63%
“…The concept of the normality of cardiac mucosa has been challenged by Chandrosoma and associates (115,116). They studied the gastroesophageal junction region in unselected adult autopsies and found that when one section was taken through this region, 29% of cases had no cardiac or cardiofundic mucosa, 44% of cases had cardiofundic mucosa only, and only 29% of cases had a zone of pure cardiac mucosa.…”
Section: Status Of the Cardiac Mucosa-does It Exist?mentioning
confidence: 99%
“…14,15 For OCT to be a reliable, sensitive, and cost-effective screening instrument, characterization of epithelial architecture at the SCJ should be accurate enough to distinguish premalignant (SIM) from benign tissue. The aim of this study was to identify and validate OCT image criteria of SIM, permitting its distinction from nonmetaplastic tissue at the gastroesophageal junction.…”
mentioning
confidence: 99%